Piperidine-based natural products targeting type IV pili antivirulence: a computational approach - SARIYAR AKBULUT, BERNA; ÖZBEK SARICA, PEMRA (My University, 2023)
© 2022 Elsevier Inc.Type IV (T4) pilus is among the virulence factors with a key role in serious bacterial diseases. Specifically, in Neisseria meningitidis and Pseudomonas aeruginosa, it determines pathogenicity and causes infection. Here, a computational approach has been pursued to find piperidine-based inhibitor molecules against the elongation ATPase of T4 pili in these two selected pathogens. Using the modeled structures of the PilF and PilB ATPases of N. meningitidis and P. aeruginosa, virtual library screening via molecular docking has returned inhibitor molecule candidates. The dynamics of the best three binders have further been investigated in detail via molecular dynamic simulations. Among these, ligands with COCONUT IDs CNP0030078 and CNP0051517 were found to have higher potential in the inhibition of ATPases based on molecular dynamic simulation analysis and biological activity information. The obtained results will guide future efforts in antivirulence drug development against T4 pili of N. meningitidis and P. aeruginosa.
Keywords: Bilgisayar Bilimleri; Bilgisayar Grafiği; Kimya; Fizikokimya; Spektroskopi; Temel Bilimler; Mühendislik ve Teknoloji; Computer Sciences; Computer Graphics; Chemistry; Physical Chemistry; Spectroscopy; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Bilgisayar Bilimi; Malzeme Bilimi; BİLGİSAYAR BİLİMİ, İNTERDİSİPLİNER UYGULAMALAR; SPEKTROSKOPİ; KİMYA, FİZİKSEL; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); COMPUTER SCIENCE; MATERIALS SCIENCE; CHEMISTRY; COMPUTER SCIENCE, INTERDISCIPLINARY APPLICATIONS; SPECTROSCOPY; CHEMISTRY, PHYSICAL; MATERIALS SCIENCE, MULTIDISCIPLINARY; Fizik Bilimleri; Fiziksel ve Teorik Kimya; Bilgisayar Grafikleri ve Bilgisayar Destekli Tasarım; Malzeme Kimyası; Physical Sciences; Physical and Theoretical Chemistry; Computer Graphics and Computer-Aided Design; Materials Chemistry; Antivirulence; Drug discovery; Molecular docking; Molecular dynamics simulations; Natural product; PilB; PilF; Piperidine; Type IV pili; Virtual library screening; Drug discovery; Molecular docking; Molecular dynamics simulations; Natural product; PilB; PilF; Piperidine; Type IV pili; Virtual library screening